Decision Support System for Municipal Energy Utilities: Approach, Architecture, and Implementation. Issue 9 (13th August 2019) - Kühne, Stefan; Scheller, Fabian; Kondziella, Hendrik; Reichelt, David Georg; Bruckner, Thomas
Abstract: To support decision makers of municipal energy utilities regarding future portfolio management, the mathematical optimization model IRPopt was developed which allows a policy‐oriented, technology‐based, and actor‐related assessment of varying energy system conditions and innovative business models. The IRPopt software environment is described and demonstrated in that the model is embedded in. To fulfill usability, flexibility, and scalability related requirements in practical usage scenarios, it hides the dry formalism of the optimization model and reduces configuration efforts by providing mechanisms to reuse configuration knowledge. Furthermore, required model expansions can be realized independently from the software engineering process due to a model‐driven deployment approach. Abstract : The mathematical optimization model IRPopt was developed in order to support decision makers of municipal energy utilities concerning future portfolio management. This model allows a policy‐oriented, technology‐based, and actor‐related assessment of varying energy system conditions and innovative business models. Model expansions can be realized independently from the software engineering process.